Benak (The Cyan Series) - Mohamad Faizuan, Mat (2025)
"Benak The Cyan Series" by Mohamad Faizuan Mat is a compelling artwork featured in the "Neighbour in Heart, Friendship in Art" exhibition at the Borneo Culture Museum, Sarawak. Presented between June 20 and 26, 2025, the series explores themes of cultural identity, community, and the fluidity of emotions through a vibrant cyan palette. Rooted in regional narratives, the piece invites viewers to reflect on the interconnectedness of neighbors and the shared human experience across diverse cultures. Organized by the Sarawak Artist Society in collaboration with Brunei Artists, this exhibition underscores the importance of friendship and understanding in the artistic dialogue among Southeast Asian communities.